Exciton condensation in quantum wells: Quantum Effects in Semiconductors and Insulating Materials - Sugakov, V.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The theory of exciton condensation is given in two-dimensional systems under suggestion that condensation occurs in really space and condensed phase arises as a result of an attractive interaction between excitons. Due to the finite value of exciton lifetime the sizes of exciton condensed phase regions are restricted and the condensed phase appears in a form of system of islands amid exciton gas. The joint solution of kinetic equations for island size and exciton diffusion equation in the space between islands has been obtained. The theory is applied to explanation of experimental manifestation of condensed phase in quantum wells and also to explanation of the periodical fragmentation, which was observed in luminescence spectrum from a ring around a laser spot in a crystal with double quantum wells. For such explanations the theory does not require the exciton Bose–Einstein condensation.